Status of Ethiopian indigenous Sheko cattle breed and the need for participatory breed management plan - Taye, T.; Ayalew, W.; Hegde, B.P. (2009)
This paper presents a framework for Community Based Management (CBM) of indigenous cattle in Dano district of West Shoa Zone in Central Ethiopia. Results of multi-disciplinary research conducted over three years served as a foundation for this framework. It outlines the essential activities and components needed to be considered to empower the cattle keeping community for effective collective action in the conservation and sustainable use of indigenous cattle. Community based initiatives stand a better chance of success with positive effect on the sustainable use of the genetic resources under stressful environments. CBM of animal genetic resources (AnGR) is responsive to the dynamism within the community, AnGR and the eco-system. The most important institutions with strong bearing on the community’s management of AnGR are the informal institutions (herding groups, social gatherings, etc.), the formal institutions in the locality (cooperatives, financial or religious institutions, etc.), the market, the administrative (political) entities, the research and extension institutions, and the interactions among the crop, natural resource and livestock sub-systems. Assumptions of favorable political environment, complementarity among the different stakeholders, continuous capacity building, and access to comprehensive market information were made in developing this framework.